Міжгалузеві терміни в українській науково-технічній термінології - Кримець, Оксана Михайлівна (Харківський національний педагогічний університет ім. Г. С. Сковороди, 2020)
Анотована стаття присвячена дослідженню міжгалузевих термінів, що вживаються в українській науково-технічній термінології з одним або кількома значеннями. З’ясовано, що поява таких одиниць пов’язана з розгалуженістю та реінтеграцією науково-технічних знань. Проаналізовано значення міжгалузевих спеціальних одиниць в різних сферах науки і техніки. Доведено, що досліджувані одиниці вживаються як у близьких, так і у віддалених науково-технічних галузях. За семантичною ознакою виокремлено три типи міжгалузевих спеціальних одиниць: терміни-еврисеманти, терміни-полісеманти, терміни-омоніми.

The relevance of the research lies in the study of intrasystem potentialities of scientific and technical terms, which are a powerful source of the development of terminology and the emergence of interdisciplinary terms used in various fields of science and technology in one or more meanings. The purpose of the article is to study the specific features of interdisciplinary terms, find out the peculiarities of the development of their meanings, identify common features, analyse definitions in various fields of science and technology, as well as to determine the types of interdisciplinary terms. The study clarifies the specific features of interdisciplinary terms that are used with different meanings in several industries or denote one broad concept used in many scientific and technical fields. There are three types of interdisciplinary terms: 1. Eurosemy terms, which have a wide meaning and are used in many scientific and technical fields. Such units denote a variety of special subjects, processes, and patterns in various fields of science and technology. 2. Polysemantic terms used in different scientific and technical fields with different meanings that are interconnected. The emergence of such terms is caused by the development of intrasystem potentialities of terminology and the reterminologization of special names. 3. Terms-homonyms used in different fields and whose meanings are not related. Such terms occur either as a result of splitting of the meanings of polysemantic words, or due to the coincidence of two or more words. Interdisciplinary terms are the result of the reintegration of special units from different scientific and technical fields. Under the influence of external and internal linguistic factors, the meanings of existing terms are reinterpreted, which leads to the emergence of new meanings that represent the concepts of other areas. As a result, there are interdisciplinary terms that denote the concepts of both similar and different spheres of human activity.
Interdisciplinary terms in Ukrainian scientific and technical terminology
Keywords: ретермінологізація; лінгвістика; терміни-еврисеманти; терміни-полісеманти; терміни-омоніми; interdisciplinary term; eurosemy term; polysemantic term; term-homonym; reterminologization